"Like Having New Batteries Installed!": Problematizing the Category of the "40+ Mother" in Contemporary Danish Media. Issue 3 (2nd July 2016) - Lahad, Kinneret; Madsen, Karen Hvidtfeldt
Abstract: In recent years, the phenomenon of the "40+ mother" has generated much media attention in Denmark. Within these discussions, 40+ mothers are regularly labelled as ridiculous, bad, or irresponsible, their access to assisted reproductive technologies is restricted, and their right to them is questioned. This rhetoric is explored here within the particular context of the Danish welfare state, which commonly takes pride in being family-friendly and is often seen as liberal in terms of its gender policies. This paper analyses these debates and argues that the ideological category of the "old mother" is another formulation of sexist and ageist discourses that identify feminine ageing with decline and emptiness. Drawing on feminist age studies, these media representations are considered here as a manifestation of middle-ageism, in which 40+ mothers undergo a process of accelerated ageing as they fail to act their age. The analysis traces these emerging discourses and discusses some of the alternatives they raise. The paper is situated within social and feminist studies of time that aim to challenge normative reproductive temporalities and the ideology of ageing as decline, so that the category of 40+ mothers opens up new rhythmic options for reproductive time and for heteronormative life-course paradigms more generally.